2022
DOI: 10.1186/s12934-022-01996-x
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and reverse engineering in Saccharomyces cerevisiae reveals a Pdr1p mutation-dependent mechanism for 2-phenylethanol tolerance

Abstract: Background 2-Phenylethanol (2-PE), a higher alcohol with a rose-like odor, inhibits growth of the producer strains. However, the limited knowledge regarding 2-PE tolerance mechanisms renders our current knowledge base insufficient to inform rational design. Results To improve the growth phenotype of Saccharomyces cerevisiae under a high 2-PE concentration, adaptive laboratory evolution (ALE) was used to generate an evolved 19–2 strain. Under 2-PE s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…With this thermal study, Dallinger showed that all evolved organisms were able to survive at 70 °C, in opposition to the initial ones. Reports of ALE employing S. cerevisiae and Escherichia coli , the most well-known species within the yeast and bacteria groups, respectively, alongside microalgae, viruses, and mammalian cell lines, have grown exponentially in recent years [ 3 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Yeasts As Attractive Biological Models For Adaptive Laborato...mentioning
confidence: 99%
See 1 more Smart Citation
“…With this thermal study, Dallinger showed that all evolved organisms were able to survive at 70 °C, in opposition to the initial ones. Reports of ALE employing S. cerevisiae and Escherichia coli , the most well-known species within the yeast and bacteria groups, respectively, alongside microalgae, viruses, and mammalian cell lines, have grown exponentially in recent years [ 3 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Yeasts As Attractive Biological Models For Adaptive Laborato...mentioning
confidence: 99%
“…During the evolutionary process, aliquots of the evolving populations are usually stocked in glycerol (within 10% to 40%, v/v ) and maintained at −80 °C for further phenotypic analysis [ 35 , 36 , 37 ]. The primary advantages are that this strategy is very easy to set up and use, requires low-cost equipment, can usually be executed by a single operator, and can be adapted to massive parallel cultures [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], as summarized in Table 1 . However, batch cultures are more susceptible to random drift due to certain shortfalls, which include variations in the population density, growth rates, and different nutrient supplementations, together with fluctuations in environmental conditions [ 29 ].…”
Section: Current Status and Applications Of Ale In Biotechnologymentioning
confidence: 99%
“…We used ChimeraX v1.5 153 to visualize Pdr1p amino acid changes we found throughout the experimental evolution and other mutations found in the literature [75][76][77][78][79] (Source Data 2) on the AlphaFold 154,155 generated structure for Pdr1p (AF-P12383-F1, Source Data 3). Subsequently, we analyzed Pdr1 Nakaseomyces glabratus protein by superimposing structures and amino acid changes 80,83,84 across species (Source Data 4; AF-B9VI40-F1, Source Data 5).…”
Section: Validation Of the Adaptiveness Of Mutationsmentioning
confidence: 99%
“…17 The transcription factor Pdr1p mutation (C862R) was reported to increase unsaturated fatty acid/saturated fatty acid ratio by 42%, decrease cell membrane damage by 81% and increase the 2-phenylethanol tolerance of S. cerevisiae. 18 The study reported here investigated the effect of engineering unsaturated fatty acid synthesis on the stress tolerance in yeast. Two desaturase genes, OLE1 and FAD2 from Z. rouxii, were overexpressed singly or simultaneously in S. cerevisiae to construct recombinant cells.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, antioxidant dipeptides have also been reported to improve the cell membrane integrity of Saccharomyces pastorianus by increasing the proportion of unsaturated fatty acids and regulating the expression of key genes in fatty acid synthesis, such as the expression of genes ACC1 and HFA1 17 . The transcription factor Pdr1p mutation (C862R) was reported to increase unsaturated fatty acid/saturated fatty acid ratio by 42%, decrease cell membrane damage by 81% and increase the 2‐phenylethanol tolerance of S. cerevisiae 18 …”
Section: Introductionmentioning
confidence: 99%